Formal methods for future interoperability - Davies, J; Gibbons, J (2009)
Interoperability is a key challenge in software engineering, whether expressed in terms of the compatibility of different systems and protocols, in terms of compliance to industry standards, or - increasingly - in terms of the ability to share and re-use data gathered in different contexts. Formal methods are mathematical techniques for the precise description of systems properties and behaviour, and have an important role to play in the future provision of interoperable systems and data. This paper describes that role, and examines the implications for present-day training and education.